Isoxazole-containing neonicotinoids: Design, synthesis, and insecticidal evaluation. Issue 4 (15th February 2018) - Lei, Chao; Geng, Li; Xu, Xiaoyong; Shao, Xusheng; Li, Zhong
Graphical abstract: Abstract: A series of novel isoxazole-containing neonicotinoids were synthesized from nitromethylene analogues and aromatic aldehydes in the presence of l -proline/K2 CO3 . Bioassays indicated that several synthesized compounds showed 40–70% mortality against brown planthopper ( Nilaparvata lugens ) under the concentration of 4 mg L −1, higher than that of imidacloprid (20%). Against cowpea aphid ( Aphis craccivora ), the best activity of title compounds reached 90% at the concentration of 20 mg L −1 .